2015
DOI: 10.1149/2.0461512jes
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Coke Type, Microstructure and Anodic Reaction Overpotential in Aluminium Electrolysis

Abstract: 20Although the anode process during aluminium electrolysis has a substantial 21 overpotential that increases the energy demand and production cost of aluminium, 22properties of the coke that can influence the electrochemical reactivity in the 23 industrial anode itself have not been well documented.In this work the 24 electrochemical performance of anodes fabricated from single source (anisotropic and 25 2 isotropic) cokes, including an ultrapure graphite as reference material, was 26 determined, and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Thorne et al reported similar trends. [14,15] The inverted horizontal anode has similar behavior to the vertical anode at current densities > 0.5 A cm À2 , i.e., random potential oscillation, and at lower current densities (0.1 to 0.3 A cm À2 for vertical and 0.1 to 0.5 A cm À2 for inverted horizontal anode) saw-tooth features are present. However, inverted horizontal anode has larger noise as discussed below.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thorne et al reported similar trends. [14,15] The inverted horizontal anode has similar behavior to the vertical anode at current densities > 0.5 A cm À2 , i.e., random potential oscillation, and at lower current densities (0.1 to 0.3 A cm À2 for vertical and 0.1 to 0.5 A cm À2 for inverted horizontal anode) saw-tooth features are present. However, inverted horizontal anode has larger noise as discussed below.…”
Section: Resultsmentioning
confidence: 94%
“…The height for the vertical anode was only 5 mm but still considered to be comparable to the other anodes as the bubbles on the vertical surface have been reported to be relatively small and this design was earlier successfully used. [13,15] Experiments were performed under inert N 2 atmosphere in a cryolite melt. The cryolite was supplied from Sigma Aldrich (purity ‡ 97 pct, cryolite ratio = 3).…”
Section: Methodsmentioning
confidence: 99%
“…The works of many researchers [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] are devoted to the anodic overvoltage measurements. For a given current density, the overvoltage values differ greatly for differently graphitized materials and for different classes of structural ordering.…”
Section: Introductionmentioning
confidence: 99%
“…According to the different researchers [10,11,23], there is a significant difference in the magnitude of overvoltage even for one class of carbon materials; the difference in overvoltages can reach more than 300 mV when measured on samples made from different industrial anode blocks. It can be assumed that in different experiments carbon materials of different degree of graphitization, as well as with different content of impurities, were used, which, apparently, affected the structure of surface layers and their reactivity [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The exact reason for these observed differences is not known and are beyond the scope of this study. A more detailed investigation of the material properties is provided in a previous work(53), and this showed that the anisotropic coke had a higher ratio of basal surface planes as well as lower amount of surface oxides (0.02 g/m 2 for the anisotropic coke and 0.035 g/m 2 for the isotropic coke). These material property differences observed in the coke may provide an explanation to the observed differences in electrochemical behavior and wetting properties of the anodes.The results obtained in this work indicate that there might be benefits from introducing isotropic cokes in industrial scale cells with respect to a reduction of the cell voltage/voltage oscillation amplitude.…”
mentioning
confidence: 96%